ISOLASI DAN KARAKTERISASI ENZIM SELULASE - masfufatun masfufatun (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2009)
Carboxy Methyl Cellulose (CMC) is a derivative of cellulose soluble in water. Therefore, CMC easily hydrolyzed into simple sugars by the enzyme cellulase. Snails are animals soft, easy to breed and utilize cellulose as a source of energy and protein content is high enough. Therefore, snails can be used as a source of cellulase enzyme to hydrolyze carboxy Methyl Cellulose (CMC) This research aims to isolate cellulase enzyme from the snail, Achatina fulica and determine itscharacterization. Glucose levels produced from cellulose enzyme activity were analyzed by using the method Semogy-Nelson. From this research it turns out cellulase enzyme isolated from hepatopankreas snail, Achatina fulica has a specific activity of 2.85 U / mg protein and activity 50oCdan temperature optimum at pH 5.16 and have had kinetic parameters Vm price of 0.23 mg / mLper minute and Km is 0.53 mg / mL. Part enzyme cellulose getting fed at a concentration of 4%.